Esophageal Myotomy pada Achalasia - Nadhia Khairunnisa; Yusmaidi (Medula, 2020)
Achalasia is a rare esophageal motility disorder that results from decreased or the absence of ganglion-blocking cells in the esophageal myenteric plexus and lower esophageal sphincter (LES). This results in the inability of the LES to relax as well as the dysfunction of the esophagus. Patients usually present with symptoms of dysphagia. Surgical therapy in Achalasia is known as Heller myotomy (Esopageal myotomy), a procedure in which the muscles around the esophagus are opened and cut. Conventional surgery uses a long incision in the chest and abdomen provides a very good result in decresing the symptoms, with a efficacy level from 88% to 95% and lasting for 6 to 10 years. For example, in the case of Mr. Y, 51 years old came with disfagia since approximately 1 year ago. The patient also complained losing weight for 10kg in the past 6 months. The physical examination of the patient are compost mentis. Blood pressure 170/100 mmHg, heart rate 80x / minute, respiratory rate 20x / minute, temperature 37.0oC. Examination of extremities and neuromuscular are normal. At radiological examination, a rontgent was obtained with the appearance of an esophageal dilatation.